1992
DOI: 10.1017/s0022149x00012633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the organophosphorous insecticide, chlorpyrifos (Dursban), on growth, fecundity and mortality ofBiomphalaria alexandrinaand on the production ofSchistosoma mansonicercariae in the snail

Abstract: Exposure ofBiomphalaria alexandrinato sublethal concentrations (0·125, 0·25 and 0·05 ppm) of the organophosporous insecticide, chlorpyrifos (Dursban), induced a reduction in egg production and egg hatchability. Exposure ofSchistosoma mansonimiracidia to the insecticide (60 min, 0·05 ppm) prior to infection ofB. alexandrinadid not affect the subsequent production of cercariae. However, exposure ofS. mansoni—infected snails to the insecticide until day 55, from day 20 to day 62 and from day 35 to 62 following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Dutta et al [2] suggested that a behavioral bioassay would be more sensitive than other types of testing methods. A numerous accounts of behavioral research on effects of toxic chemicals at low concentrations have been reported in various taxa, including crustaceans [3,4], snails [5], fish [6] and insects [7,8]. Recently Oshima et al [9] observed suppression of sexual behavior in male medaka exposed to estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…Dutta et al [2] suggested that a behavioral bioassay would be more sensitive than other types of testing methods. A numerous accounts of behavioral research on effects of toxic chemicals at low concentrations have been reported in various taxa, including crustaceans [3,4], snails [5], fish [6] and insects [7,8]. Recently Oshima et al [9] observed suppression of sexual behavior in male medaka exposed to estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…no escape) and are exposed to a constant level of chemical stress, every organism has its own ability to adapt to the environmental stress by intrinsic modification, which might induce stepwise BRs including behavior stimulation, acclimation, adjustment and so on (Sun et al, 1993;Zhang et al, 2012). By far, BR of various taxa, including crustaceans (Billoir et al, 2007;Kim et al, 2006;Roast et al, 2000), snails (Coffin et al, 2008;Ibrahim et al, 1992), insects (Chon et al, 1998;Ji et al, 2007), and fish (Gray et al, 1999;Liu et al, 2011;Moore and Waring, 1996), has been reported to be sensitive to sublethal exposures to numerous chemical pollutants, which have drawn attention as a means of developing a biomonitoring tool for detecting toxic chemicals in the environment. In fact, as an efficient tool for biomonitoring in aquatic ecosystems, the automatic detection of response behaviors has received considerable attention since 1980s (Lemly and Smith, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, behavioral response has been suitable in addressing toxicological impact assessment in all of the test endpoints [1,8,14,18,32,35]. By far, behavioral response of various taxa, including crustaceans [41,25,7], snails [23,13], insects [11,24], and fish [31,16,30], has been reported to be sensitive to sublethal exposures to various chemical pollutants. Based on the concentration-response-time analysis [43,19], the assessment of toxicity of chemicals by behavioral eco-toxicology has successfully been applied in Daphnia magna [3].…”
Section: Introductionmentioning
confidence: 99%